Effect of accelerated weathering on fire performance and general composition of photovoltaic (PV) back sheets - Mohamed Muhsin Mohamed Baseer Ahamed (Nanyang Technological University, 2024)
Current fire safety regulations regarding installation of Photovoltaic (PV) panels indicate a requirement to have an unobstructed gap between the rooftop and PV panel. This is to prevent building fire from reaching the PV panels and causing outbreak, as well as electrical fire originating from PV system to reach the rooftop. In the case of Building-Integrated Photovoltaics (BIPVs) systems, PV panels are integrated into the building structure, therefore this gap is unachievable due the nature of its configuration. To improve fire resistance, a Dual-Glass PV system can be used. However, the more commonly used configuration in the industry are PV systems with a polymer based back sheet layer. This PV back sheet layer is moreover exposed to outside environments under UV exposure. Limited studies have been carried out on this layer and its fire performance after weathered conditions. This Final Year Report evaluates the effect of accelerated weathering on fire performance and general composition of PV cells back sheet, by conducting a comprehensive study using PV back sheet samples from two different manufacturers. The samples were placed in the Atlas UV accelerated weathering tester and were operated as per IEC TS 62788-7-2 standards, at cyclic exposure of UVA-340A lamps at 1.00W/m2 at 65°C for 8 hours, and condensing humidity at 50°C in the dark for 4 hours, with water spray of 0.15 hours. They were categorized and removed at periodic intervals up to 1000hrs, and subsequently characterized through DSC, FTIR, TGA and tensile testing before flame test was carried out. Results from characterization tests of FTIR indicated chemical degradation due to UV exposure for both samples, with peak at 2928〖cm〗^(-1), indicating formation of Ar-Ch_3 group due to photolysis after UV exposure. Flame test results from the experimental setup indicated that the 1000 hours exposed samples exhibited a shorter flame propagation time compared to unweathered samples. This suggests that accelerated weathering could influence flame propagation of the PV back sheets, although the quality of data can be improved by using sample with a larger dimension to adhere to current test standards.